2022
DOI: 10.1163/15685411-bja10145
|View full text |Cite
|
Sign up to set email alerts
|

The ability of Meloidogyne javanica to suppress salicylic acid-induced plant defence responses

Abstract: Summary Suppression of the defence system of plants by some plant pathogens is an important mechanism of their parasitism, and plant-parasitic nematodes use several mechanisms to affect different parts of the plant defence system. This study was designed to investigate the ability of a root-knot nematode, Meloidogyne javanica, to reduce or suppress the plant (tomato) immune system, before or after activation by a strong inducer, salicylic acid (SA). The experimental treatments were tomato plants inoculated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…Based on these results, it is likely that the expression levels of other SA-responsive genes are also constitutively higher in ALYSTE F-1 at 14 DAI, which ultimately delays the development of M. javanica and reduces the nematode reproduction rate (Table 2). Several studies have shown that the application of SA, or chemicals with a similar action, can reduce nematode infection [23,[37][38][39]41,42]. Qtu et al (1997) [90] described an important role of chitinases in a resistant soybean cultivar during the M. incognita infection, and concluded that JA and SA pathways are likely involved in soybean resistance response.…”
Section: Sa-related Responses In the Roots Of Alyste F-1 And Dutch Mo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these results, it is likely that the expression levels of other SA-responsive genes are also constitutively higher in ALYSTE F-1 at 14 DAI, which ultimately delays the development of M. javanica and reduces the nematode reproduction rate (Table 2). Several studies have shown that the application of SA, or chemicals with a similar action, can reduce nematode infection [23,[37][38][39]41,42]. Qtu et al (1997) [90] described an important role of chitinases in a resistant soybean cultivar during the M. incognita infection, and concluded that JA and SA pathways are likely involved in soybean resistance response.…”
Section: Sa-related Responses In the Roots Of Alyste F-1 And Dutch Mo...mentioning
confidence: 99%
“…Salicylic acid is a major defense hormone against biotrophic and hemibiotrophic pathogens [36]. The application of SA, or chemicals with similar actions, can reduce nematode infection, and in many cases, nematodes are able to suppress the SA pathway [5,15,35,[37][38][39][40][41][42]. Previous studies have shown that mutants or transgenics with lower SA levels or signaling are more sensitive to nematode attack [37,38], whereas increased SA levels or signaling reduces nematode infestation [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%